The Australian Aboriginal Birth Cohort study: socio‐economic status at birth and cardiovascular risk factors to 25 years of age. Issue 6 (22nd July 2019) - Juonala, Markus; Sjöholm, Pauline; Pahkala, Katja; Ellul, Susan; Kartiosuo, Noora; Davison, Belinda; Singh, Gurmeet R
Abstract: Objectives: To determine whether socio‐economic status at birth is associated with differences in risk factors for cardiovascular disease — body mass index (BMI), blood pressure, blood lipid levels — during the first 25 years of life. Design: Analysis of prospectively collected data. Setting, participants: 570 of 686 children born to Aboriginal mothers at the Royal Darwin Hospital during 1987–1990 and recruited for the Aboriginal Birth Cohort Study in the Northern Territory. Participants resided in 46 urban and remote communities across the NT. The analysed data were collected at three follow‐ups: Wave 2 in 1998–2001 (570 participants; mean age, 11 years), Wave 3 in 2006–2008 (442 participants; mean age, 18 years), and Wave 4 in 2014–2016 (423 participants; mean age, 25 years). Main outcome measures: Cardiovascular disease risk factors by study wave and three socio‐economic measures at the time of birth: area‐level Indigenous Relative Socioeconomic Outcomes (IRSEO) index score and location (urban, remote) of residence, and parity of mother. Results: Area‐level IRSEO of residence at birth influenced BMI ( P < 0.001), systolic blood pressure ( P = 0.024), LDL‐cholesterol ( P = 0.010), and HDL‐cholesterol levels ( P < 0.001). Remoteness of residence at birth influenced BMI ( P < 0.001), HDL‐cholesterol ( P < 0.001), and triglyceride levels ( P = 0.043). Mother's parity at birth influenced BMI ( P = 0.039). Conclusions: Our longitudinal life course analyses indicate that area‐level socio‐economic factors at birth influence the prevalence of major cardiovascular disease risk factors among Indigenous Australians during childhood and early adulthood.